What is done with questionable foods? The infant formula example - Kent, George (World Nutrition, 2019)
What is done with foods of questionable quality such as those that are outdated or recalled? There is no agency of government that tracks such foods, so they might re-enter the food stream, whether legally or illegally. This can put people’s health at risk. This is a major issue in relation to infant formula because infants are highly vulnerable and for a time formula can constitute their entire diet. There is a need for clear law for the management of questionable foods and for active enforcement of the law. There is also a need for transparency for the entire process of handling questionable foods.